A conceptual framework for selecting appropriate populations for public health interventions - Jens Aagaard-Hansen; Jens Aagaard-Hansen; Anette Lykke Hindhede; Anette Lykke Hindhede; Helle Terkildsen Maindal; Helle Terkildsen Maindal (Frontiers Media S.A., 2023)
This article suggests a conceptual framework for choice of target populations for public health interventions. In short, who should benefit? Taking the seminal work of Geoffrey Rose on "individuals at risk" versus the "whole population approach" as a point of departure, we explore later contributions. Frohlich and Potvin introduced the notion of "vulnerable populations" applying relevant social determinants as the defining selection criterion. Other interventions focus on a "physical space" (spatial demarcations) such as a neighborhood as a means to define intervention populations. As an addition to these criteria, we suggest that the life-course perspective entails an alternative means of selecting target populations based on a "temporal" perspective. A focus on the various age phases ranging from fetal life and infancy to old age may guide selection of population segments for targeted public health interventions. Each of the selection criteria has advantages and disadvantages when used for primary, secondary, or tertiary prevention. Thus, the conceptual framework may guide informed decisions in public health planning and research regarding precision prevention versus various approaches to complex community-based interventions.